Long-Term Exposure to Fine Particulate Matter and the Deterioration of Estimated Glomerular Filtration Rate: A Cohort Study in Patients With Pre-End-Stage Renal Disease - Wu, Yu-Hsien; Wu, Chih-Da; Chung, Mu-Chi; Chen, Cheng-Hsu; Wu, Laing-You; Chung, Chi-Jung; Hsu, Hui-Tsung (Frontiers in Public Health, 2022)
Limited literature has explored the effect of air pollutants on chronic kidney disease (CKD) progression, especially for patients with pre-end-stage renal disease (pre-ESRD). In this study, we reported the linear and nonlinear relationships of air pollutants of particles with diameter <2.5 μm (PM2.5) and nitrogen dioxide (NO2) with estimated glomerular filtration rate (eGFR) deterioration after adjusting for smoking status and other traditional clinical factors. This study adopted a retrospective cohort of patients with stage 3b to stage 5 CKD (N = 11,479) from Taichung Veterans General Hospital during January 2006 to December 2020. The eGFR deterioration was defined as a decline in eGFR > 5 ml/min/1.73 m2/year. Hybrid kriging/land-use regression models were used to estimate the individual exposure levels of PM2.5 and NO2. The relationships of air pollutants with eGFR deterioration were evaluated using Cox proportional hazard models. After adjusting for smoking status, baseline eGFR stages, and other traditional clinical factors, the risk of eGFR deterioration was found to increase with increasing PM2.5 and NO2 level (p < 0.0001 and p = 0.041, respectively), especially for those exposed to PM2.5 ≥ 31.44 μg/m3 or NO2 ≥ 15.00 ppb. Similar results were also found in the two-pollutant models. Nonlinear dose–response relationships of eGFR deterioration were observed for concentrations of 26.11 μg/m3 for PM2.5 and 15.06 ppb for NO2. In conclusion, linear and nonlinear associations between PM2.5 and NO2 levels and the incidence risk of eGFR deterioration were observed in patients with pre-ESRD.